2006
DOI: 10.1002/adsc.200606198
|View full text |Cite
|
Sign up to set email alerts
|

An Inexpensive and Efficient Copper Catalyst for N‐Arylation of Amines, Amides and Nitrogen‐Containing Heterocycles

Abstract: An inexpensive and efficient catalyst system has been developed for the N-arylation of nitrogen-containing compounds including a variety of amines, amides, indole and imidazole. This simple protocol uses CuI as the catalyst, commercial available pipecolinic acid as the new ligand, K 2 CO 3 as the base and DMF as the solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…Other N-donor ligands, mostly imidazoles, and Odonors were tested and showed no improved performance ( Table 1, entries [4][5][6][7][8][9][10][11][12]. Amino acids, like proline 15 and pipecolinic acid, 16 which have been successfully used as ligands in aryl halide aminations, were also tested in the model reaction, but gave no diaryl ether coupling product. Variation of bases revealed that Cs 2 CO 3 also led to good results (Table 1, entry 13), comparable to dry K 3 PO 4 , which must be handled under strict exclusion of moisture (Table 1, entries 14 and 15).…”
mentioning
confidence: 99%
“…Other N-donor ligands, mostly imidazoles, and Odonors were tested and showed no improved performance ( Table 1, entries [4][5][6][7][8][9][10][11][12]. Amino acids, like proline 15 and pipecolinic acid, 16 which have been successfully used as ligands in aryl halide aminations, were also tested in the model reaction, but gave no diaryl ether coupling product. Variation of bases revealed that Cs 2 CO 3 also led to good results (Table 1, entry 13), comparable to dry K 3 PO 4 , which must be handled under strict exclusion of moisture (Table 1, entries 14 and 15).…”
mentioning
confidence: 99%
“…However, only electron -rich anilines gave complete conversion, while electron -defi cient anilines provided low yields. Fu found that this drawback could be overcome by heating at 110 ° C and using pipecolinic acid ( L5 ) as a ligand (entry 2) [12] . Similar studies were reported by Liu and coworkers in which DMEDA ( L11 ) was found to be a better ligand (entry 3) [13] .…”
Section: Arylation Of Aryl Aminesmentioning
confidence: 99%
“…The amino acid ligands L5 and L6 showed total conversion and provided better yields than 1,2-diamine-based ligands (L2, L3 and L4, entries 10-12). In particular, L6 [17] was superior among the ligands examined at 100 8C, providing 2a in 87% yield (entry 14). It seems that both the N À H and carboxylate functional groups of this ligand are important to the activity of the catalysts derived from it.…”
Section: Introductionmentioning
confidence: 96%